Exploring New Frontiers in Human Resource Management: A Systematic Literature Review on the Evolving Role of HR Champions - Nurmansyah, Abdul Ahmad Hafidh; Senen, Syamsul Hadi (GoAcademica Research & Publishing, 2023)
This systematic literature review critically examines the evolving role of Human Resource (HR) champions in the dynamic landscape of Human Resource Management (HRM). Amidst the rapidly changing organizational environments, the function of HR has transcended traditional boundaries, necessitating a reevaluation of its strategic roles and competencies. This review synthesizes findings from a diverse range of scholarly articles, focusing on the period from 2010 to 2023, to delineate the emerging trends and challenges in HRM. Utilizing rigorous selection criteria, this study identifies and analyzes key themes, including the integration of technology in HR practices, the shift towards strategic HRM, and the increasing importance of HR in organizational resilience and employee well-being. The findings reveal a paradigm shift in the role of HR professionals, highlighting their critical function as strategic partners, change agents, and employee advocates. This review contributes to the existing body of knowledge by offering a comprehensive understanding of the contemporary HR landscape, providing valuable insights for academics, practitioners, and organizations seeking to leverage HR capabilities in achieving strategic objectives. The study also identifies gaps in the current literature and suggests directions for future research, emphasizing the need for empirical studies to further explore the impact of these evolving roles on organizational performance.